Laparoscopic and open gastrectomy for locally advanced gastric cancer: a retrospective analysis in Colombia - Maritza Romero-peña; Liliana Suarez; Diego Efraín Valbuena; Carlos Eduardo Rey Chaves; Danny Conde Monroy; Raúl Guevara (BMC Surgery, 2023)
Abstract Introduction Radical gastrectomy has traditionally been the pillar treatment with curative intent for malignant tumors of the stomach. The safety of the laparoscopic approach for advanced gastric cancer (AGC) is still under debate. In our institution, laparoscopic gastrectomy is the most performed approach. Objective Our aim is to describe the experience of a high-volume center in the treatment of AGC in Colombia and to analyze the short-term results and the overall survival rate at 1, 3, and 5 years comparing the open and laparoscopic approaches. Methods A cross-sectional retrospective study of patients who underwent gastrectomy for advanced gastric cancer by open or laparoscopic approaches were performed. A Will-Coxon Mann Whitney test was performed in terms of lymph node status and surgical approach. Survival analysis was performed using the Kaplan–Meier method for overall survival at 1, 3, and 5 years. An initial log-rank test was performed to test the relationships between the operative variables and overall survival, the statistical value was accepted if p < 0.20. Data with an initial statistical relationship in the log-rank test were included in a secondary analysis using multivariate Cox proportional regression, variables with a value of p < 0.05 were considered statistically significant. Results 310 patients met the inclusion criteria. 89% underwent laparoscopic gastrectomy and 10.9% open gastrectomy. The resection margins were negative at 93.5% and the In terms of lymph node dissection, the median lymph nodes extracted was 20 (12;37), with statistically significant differences between the approaches in favor of the laparoscopic approach (Median 21 vs 12; z = − 2.19, p = 0.02). The survival rate was at 1, 3, and 5 years of 84.04%, 66.9%, and 65.47% respectively. The presence of complications and the ICU requirement have a negative impact on survival at 1 year (p 0.00). Conclusion A laparoscopic approach is safe with acceptable morbidity and mortality rates for treating gastric cancer. D2 Lymphadenectomy could be performed successfully in a laparoscopic approach in a high-volume center and a properly standardized technique. Major postoperative morbidity with intensive care unit requirement seems to influence overall survival rates.